Exit Tickets Open the Door to University Learning - Angela Danley, EdD; Ann McCoy, PhD; Rahila Weed, PhD (InSight, 2016)
Four instructors from a mid-western university implemented exit tickets in their university courses. The exit tickets were based on Marzano’s (2012) four types of exit tickets and were analyzed for patterns. Faculty completed a journal to reflect on what was learned examining the exit tickets. A survey was completed by both instructors and university students to determine the benefits of the use of exit tickets as a formative assessment at the university. Researchers share the processes used for implementing exit tickets and the results of the data collected along with implications for the use of exit tickets at the university.